ERGİYE İLİŞKİN TEBLİGAT İŞLEMİNİN ADİL YARGILANMA İLKELERİ BAĞLAMINDA DEĞERLENDİRİLMESİ - (:unkn) unknown (My University, 2018)
Hakkında tesis olunan hukuki işlemi ilgilisine bildiren tebligat,hem adli hem idari süreçte çok önemli bir görev üstlenmektedir. Tebli-gat, vergiye ilişkin işlemlerde üzerinde hassasiyetle durulması gerekenbir husustur. Zira tebligat, vergilendirme sürecine ilişkin işlemlerde mu-hatabının idari haklarını kullanmasına imkân tanımasının yanı sıra vergiyargılama sürecinde de muhatabının yargısal haklarını kullanabilmesineolanak sağlamaktadır. Bu bağlamda uzlaşma ve cezalarda indirim gibiidari hakların kullanılması, yalnızca tebligat işleminden sonra mümkünolabilmektedir. Ayrıca tebligat, ilgilisinin hem hakkında tesis olunanhukuki işlemden, hem de bu işlemin dayanağı olan hususlardan haberdaredilmesini sağlamasının yanı sıra, bu işleme karşı yargısal haklarını ka-zai mercilerde arayabilmesine ve iddialarını bu mercilerde öne sürebil-mesine de olanak tanır. Bu bakımdan tebligat, Avrupa İnsan HaklarıSözleşmesi md.6’da hüküm altına alınan adil yargılanma ilkesi ve builkeyi temellendiren diğer ilkelerle yakından ilişkilidir.

Notification of the legal proceedings concerning the establishment takes on a vital role both in judicial and administrative process. Notifi- cation is an issue that needs to be focused sensitively on transactions related to taxation process due to the fact that it allows not to use the administrative rights of the accountant in transactions related to the taxation process, but also allows the accountant to use the judicial rights in the tax prosecution process. In this context, the use of administrative rights such as reconciliation and reduction in penalties is only possible after the notification. Besides allowing the interested person to be in- formed about the legal procedure against him/her and the issues which are based on these proceedings, notification also allows its addressee to make it possible for the judicial authorities to seek judicial rights against such proceedings and to present their claims to these authori- ties. In this respect, notification is closely related to right to a fair trial in Article 6 of the European Convention on Human Rights and other rights and principles based on this rights.
EVALUATING OF THE NOTIFICATION RELATED TO TAXATION IN THE CONTEXT OF RIGHT TO A FAIR TRIAL
Keywords: Hukuk